Triple Diffusive Convection in a Fluid Layer Under an A.C Electric Field - Sureshkumar S.; Krishna B. Chavaraddi; Priya M. Gouder; G. K. Ramesh; J. K. Madhukesh; Umair Khan; Anuar Ishak; Syed Modassir Hussain (Advances in Mathematical Physics)
The effect of an imposed alternating current (A.C) electric field on the onset of convective instability in a horizontal triply diffusive fluid layer is investigated. Analytical solutions are obtained for steady and oscillatory onset when imposed gradients of the stratifying agencies are constant and vertical. It was found that A.C electric Rayleigh number did not affect the necessary conditions for oscillatory convection. The stability boundaries are drawn and it is observed that an increase in the A.C electric field strength is to hasten the onset of convection. The evolution of neutral curves is analyzed in detail by varying the A.C electric Rayleigh number and other physical parameters. For certain choices of physical parameters, it is noted that the oscillatory part will give rise to two oscillatory neutral solutions for each wave number and closed disconnected neutral curves are found to exist, suggesting the requirement for three critical Rayleigh numbers to specify the linear stability criterion.